2016
DOI: 10.1007/s00391-016-1038-9
|View full text |Cite
|
Sign up to set email alerts
|

Familienbegleitung

Abstract: The concept of family companions (Familienbegleiter) has proven to be a cost-covering model of an effective intervention based on the needs of caring families, which should become more widespread in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The findings presented contribute to our understanding of the pro- age, which has been reported as being somewhat higher (Vara, 2014;Kricheldorff & Brijoux, 2016;Santini et al, 2016). The reason for this might be that when a patient is hospitalized, the daughter TIMONET-ANDREU ET AL.…”
Section: Discussionmentioning
confidence: 56%
“…The findings presented contribute to our understanding of the pro- age, which has been reported as being somewhat higher (Vara, 2014;Kricheldorff & Brijoux, 2016;Santini et al, 2016). The reason for this might be that when a patient is hospitalized, the daughter TIMONET-ANDREU ET AL.…”
Section: Discussionmentioning
confidence: 56%
“…Several studies showed the efficacy of constructivist approaches in adult education, particularly on the transfer of knowledge in practice [137, 138]. In Germany, several approved training programs for volunteers that support the elderly already exist; they have demonstrated effectiveness among patients and include constructivist participation procedures that the herein presented concepts lacked [89, 91]. An international discussion on the (different) appropriate theoretical backgrounds of volunteer training with implications for future study designs is needed.…”
Section: Discussionmentioning
confidence: 99%